(3Jbjje GdeTQhYGJ (B:s (3JMdjd eYGjjQ h eDTQGJ OQGSGJ GdLOhi h Jbjje caGAI GdGOGA (B/s - (3GdfLGQ, jMj Zfjs ((3YeGf(B: s (3OGQ OLdI(B, s, 2010)
(3JMdjd eYGjjQ h eDTQGJ OQGSI GdLOhi , CSGdjH Jbjje GbJQGMGJ GdGfaGb GdQCSeGdj h JQJjHgG , eYjGQ GdQHMjI GdJLGQjI , eYjGQ GdQHMjI GdGbJUGOjI GdhWfjI , JMdjd eYGjjQ h eDTQGJ OQGSI Jbhje caGAI GdGOGA h eYGjjQ bjGS caGAI GdGOGA (B.s
(3eQGLY U(B.791 (3; edGMb U(B.559 (3; LOGhd U(B.818 (3; GTcGd U(B.819s
Keywords: (3GdOjhf GdNGQLjIs; (3GdeTGQjYs; (3Jbjje GdeTGQjYs